Switch from eculizumab to satralizumab in aquaporin 4 immunoglobulin G–seropositive neuromyelitis optica spectrum disorder: a case series report - Abboud, Hesham; Subei, Adnan; Sengul, Buse; Shin, Robert K.; Goulette, Paige; Walch, Rosemarie; Coté, Jeanie; Pace, Robert; Obeidat, Ahmed Z.; Ferayorni, Lisa; Gholizadeh, Shervin (Frontiers in Immunology, 2025)
ObjectivesThis case series describes adults with aquaporin 4 immunoglobulin G–seropositive (AQP4-IgG+) neuromyelitis optica spectrum disorder (NMOSD) who switched treatment from eculizumab to satralizumab.MethodsCase information for patients with AQP4-IgG+ NMOSD who received satralizumab for ≥6 months was obtained from US healthcare providers from April 2022 to January 2024. Patient characteristics, examination findings, diagnostic test results, treatment response, and adverse events were recorded.ResultsAmong the 5 patients (4 women and 1 man) included, ages ranged from 32 to 81 years and 4 patients self-identified as Black/African American and 1 as White. Time since confirmed NMOSD diagnosis ranged from 1 to 14 years. The reasons for initiating satralizumab were route of administration/patient preference (n=3) and inadequate disease control with eculizumab (n=2). The duration of satralizumab treatment was 10 to 31 months. All 5 patients were relapse-free with satralizumab, and adverse events they experienced were primarily asymptomatic laboratory abnormalities.DiscussionIn this retrospective case series, satralizumab was effective and well tolerated in patients with NMOSD who switched from eculizumab due to route of administration/patient preference or inadequate disease control. These outcomes align with the long-term efficacy and safety outcomes with satralizumab in the phase 3 SAkura clinical trials.